Mechanisms for iron toxicity tolerance in lowland rice - Audebert, A.; Sahrawat, K.L. (Informa UK Limited, 2000)
Iron toxicity is a widespread nutrient disorder of lowland rice in West Africa. Soluble iron present in the soil solution under waterlogged conditions is absorbed by roots and accumulates in leaves. It causes poor growth and tillering and severe yield reductions, associated with leaf discoloration. Field experiments were conducted during 1994–1996 at an iron‐toxic lowland site at Korhogo (Ivory Coast) to study the interactions between iron toxicity and the addition of various plant nutrients. Nine nutrient element treatments (combinations of N, P, K and Zn, including no fertilizer) were tested on one iron‐susceptible (Bouake 189) and one iron‐tolerant (CK 4) cultivar. The application of P, K and Zn with N reduced iron toxicity symptoms and increased yield in both cultivars. Strong correlations were observed between grain yield and scored leaf iron toxicity symptoms across seasons and treatments. The iron‐tolerant rice cultivar absorbed less iron or transported less from roots to leaves, indicating the presence of a physiological avoidance mechanism. At any given concentration of iron in the leaves, net photsynthetic rates were lower in the susceptible than in the tolerant cultivar. The iron‐tolerant cultivar owed its superior performance under iron‐toxic conditions partly to avoidance (less iron accumulation in leaves) and tolerance (superior photosynthetic potential in the presence of absorbed iron in the leaves). Data indicated that these mechanisms can be further enhanced through the application of P, K and Zn.